Representations of British Chinese Identities and British Television Drama: Mapping the Field. Issue 2 (April 2019) - Knox, Simone
Abstract : While important scholarship exists on the television representations of Asian American identities, research in the UK has been focused on African Caribbean and South Asian identities. Very little scholarly attention has been paid to televisual representations of British Chinese identities, despite the British Chinese constituting one of the larger and fastest growing ethnic minority groups within contemporary Britain. Informed by an understanding of the complexity of the term 'British Chinese', this article explores the representation of British Chinese identities in British television drama. Despite the long-standing absence and invisibility of such identities in British television, as perceived within the popular imagination in Britain and in British Chinese discourses, the article shows that a larger number of British Chinese actors have found notable employment in British television than is commonly acknowledged or remembered within the popular imagination. The article draws on a database that deploys a range of research, including archive research at the BFI Reuben Library, to map the presence of British Chinese actors in British television drama since 1945. Through this historiographic focus, the article identifies some of the most significant trends in representations of British Chinese identities in British television drama. It then illustrates and provides more specific texture to these broader patterns through the close textual analysis of a case study, the BBC1 flagship series Sherlock . It concludes by reflecting on the contemporary period which has seen an influx of British Chinese actors into British television drama as well as high-profile diversity campaigning within Britain.